Tempos de diálogo : o olhar dos jovens sobre suas experiências no ensino médio integrado do IFRS - Pellizzer, Camila Siqueira Rodrigues (My University, 2017)
This dissertation aims to analyze multiple dimensions of dialogue among young students of High School at Instituto Federal do Rio Grande do Sul (IFRS), Brazil, in order to identify difficulties to promote listening, as an educative and human practice, which crosses school cultures. The problem of the research – which intends to investigate how youth realize and mean dialogue in High School at IFRS in Campus X, Y, and Z – is justified by the increasing academic studies that point out several senses attributed to dialogue by youth in High School. Theoretical support for this research is based on concepts related to certain authors, such as Dayrell (2003, 2006, 2009, 2011 e 2014), Carrano, (2000, 2009), Sposito (2002), Stecanela (2006, 2010, 2013, 2016), Pais (1990, 2003 e 2005), Tomazetti (2014), Scklickmann (2010, 2012, 2014), Buber (1977, 2009), Carbonara (2013), Gadamer ( 2002, 2004, 2007), Freire (1980, 1992, 2002, 2009), Hermann (2014), for they contribute with their studies in education, sociology, and filosofy. As for the methodological procedures based on qualitative research in Education, it is adopted the technique of Focal Groups, that proposes to listen and discuss a certain subject among the participants based on Barbour (2009), Gondim (2002), Melo and Araújo (2010). while analyzing the narratives on focal groups and guided by Discursive Text Analysis, according to Moraes and Galiazzi (2006, 2011), thirteen thematic subcategories emerged, and they indicate elements that are parts of day to day of Integrated High School, but they are not always realized by their authors. These subcategories are: Youth: a state of spirit; An interconnected generation: the fear of being alone; The generational meeting: the older ones as references for juvenile relationships; A distinct high school; From engagement to compensation; The “thinking about”: an exercise for a critics conscientious; An interdisciplinary curriculum; Performable culture: a new school culture; Dialogue as a mean of approaching; Denying listening: an oppressor act; Listening and being listened; and The opportunity of learning from the group. Research results point out that, against hypothesis usually found, young people make narratives in presence of dialogue and significant practices. Besides it was possible to identify within participant school institutions a performable engaged youth, which aims to be recognized in a distinct and compensatory High School, as related to other institutions that offer this final step of Basic Education.
A presente dissertação tem como objetivo analisar as múltiplas dimensões do diálogo experienciado pelos jovens estudantes do Ensino Médio do Instituto Federal do Rio Grande do Sul (IFRS), a fim de identificar as dificuldades encontradas para a promoção da escuta, como prática humana e educativa, que transversaliza as culturas escolares. O problema de pesquisa – que pretende investigar como os jovens percebem e significam o diálogo na experiência do Ensino Médio Integrado do IFRS nos Campus X, Y e Z1 – justifica-se pelo crescimento de estudos acadêmicos que apontam diferentes sentidos atribuídos ao diálogo pelos jovens na trajetória do Ensino Médio. O aporte teórico que fundamenta esta pesquisa está alicerçado em conceitos que estão relacionados a determinados autores, como Dayrell (2003, 2006, 2009, 2011 e 2014), Carrano, (2000, 2009), Sposito (2002), Stecanela (2006, 2010, 2013, 2016), Pais (1990, 2003 e 2005), Tomazetti (2014), Scklickmann (2010, 2012, 2014), Buber (1977, 2009), Carbonara (2013), Gadamer ( 2002, 2004, 2007), Freire (1980, 1992, 2002, 2009), Hermann (2014), que trazem contribuições com seus estudos no campo da sociologia e filosofia. No que diz respeito aos procedimentos metodológicos ancorados na pesquisa qualitativa em Educação, adotou-se a técnica dos grupos focais, que propõe escutar e discutir determinado assunto entre os participantes à luz do pensamento de Barbour (2009), Gondim (2002), Melo e Araújo (2010). Na análise das narrativas, produzida nos grupos focais e orientada pela Análise Textual Discursiva de Moraes e Galliazzi (2006, 2011), emergiram treze categorias de temáticas, as quais indicam elementos que fazem parte do cotidiano do Ensino Médio Integrado, mas que nem sempre são percebidas pelos seus atores. Entre essas categorias estão Juventude: um estado de espírito; Uma geração Interconectada: o receio de ficar sozinho; O encontro geracional: os mais velhos como referências nas relações juvenis; Um Ensino Médio Distinto; Do engajamento á compensação; O “pensar sobre”: um exercício para uma consciência crítica; Um currículo voltado para Interdisciplinaridade; Cultura performativa: uma outra cultura escolar; O diálogo como meio de aproximação; Negação à escuta: um ato opressor; Escutar e ser escutado no GF e a oportunidade de aprender com o grupo. Os resultados da pesquisa sinalizam que, na contramão das hipóteses comumente encontradas, os jovens narram na presença de práticas dialógicas e significativas. Além disso, identifica-se no interior das instituições escolares participantes uma juventude performativa, engajada e que busca ser reconhecida em um Ensino Médio distinto e compensatório em relação às demais instituições que ofertam a etapa final da Educação Básica.
Keywords: Diálogo; Ensino médio; Juventude; Dialogue; High school; Youth